Chapter Le ragioni di una ricerca in una bottega del sapere del XXI secolo - Poli, Daniela (Territori, 2023)
The chapter describes coordinates, steps and goals of the research work the book results from, starting in a 2019 which represented the 500th anniversary of Leonardo's death and the first valuable opportunity for a revival of his powerful suggestions to today's transdisciplinary science.